2020
DOI: 10.1108/itp-01-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

OKC-enabled online knowledge integration: role of group heterogeneity and group interaction process

Abstract: PurposeOnline knowledge integration has been an important concern of the online knowledge community as it can lead to various positive outcomes of online knowledge coproduction. This paper identifies online knowledge integration factors by considering group heterogeneity and group interaction process.Design/methodology/approachBased on the categorization-elaboration model (CEM) and interactive team cognition (ITC) theory, a research model that reflects the antecedent's factors and mediating factors of online k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 73 publications
(96 reference statements)
0
15
0
Order By: Relevance
“…Miao et al, 2016;Pee et al, 2018;Wu et al, 2018) and some have examined the effect of contributor group heterogeneity (e.g. Qiu et al, 2020). These previous studies indicated that not all people participate to the same extent in a crowdsourcing environment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Miao et al, 2016;Pee et al, 2018;Wu et al, 2018) and some have examined the effect of contributor group heterogeneity (e.g. Qiu et al, 2020). These previous studies indicated that not all people participate to the same extent in a crowdsourcing environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2018) and some have examined the effect of contributor group heterogeneity (e.g. Qiu et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various types of group heterogeneity are studied in the literature, such as skill heterogeneity (Giuri et al, 2010), role-based heterogeneity (Daniel et al, 2013), tenure and interest heterogeneity (Ren et al, 2016) and cognitive heterogeneity (Arazy et al, 2011). Some studies have concluded that group heterogeneity is positively related to open collaboration performance (Kittur and Kraut, 2010;Wang et al, 2018), but other studies have reported that group heterogeneity is negatively related to open collaboration performance (Arazy et al, 2011;Ren and Yan, 2017;Qiu et al, 2020). These inconsistent findings seem to imply a complex relationship between group heterogeneity and open collaboration performance.…”
Section: Introductionmentioning
confidence: 99%
“…Online open collaboration is not an isolated process of cognition or interaction (Qiu et al, 2020(Qiu et al, , 2021. Instead, consideration must be given to both cognition and interaction when examining the performance of online group open collaboration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation